2004
DOI: 10.1007/978-3-540-30198-1_49
|View full text |Cite
|
Sign up to set email alerts
|

Performance Comparison of Genetic and Differential Evolution Algorithms for Digital FIR Filter Design

Abstract: Abstract. Differential Evolution (DE) algorithm is a new heuristic approach mainly having three advantages; finding the true global minimum of a multi modal search space regardless of the initial parameter values, fast convergence, and using a few control parameters. DE algorithm which has been proposed particulary for numeric optimization problems is a population based algorithm like genetic algorithms using the similar operators; crossover, mutation and selection. In this work, DE algorithm has been applied … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(25 citation statements)
references
References 3 publications
(2 reference statements)
0
25
0
Order By: Relevance
“…In order to solve the problems of GA for global optimization, Differential Evolution (DE) was proposed by Stron and Price [18,20]. Many studies have confirmed that DE is a more powerful optimization algorithm than GA, both in computation efficiency and accuracy [15,19,20,28]. Therefore, DE is employed in this paper to solve the optimization problem shown in Eq.…”
Section: Parameter Optimization Of Morlet Wavelet Filter and Flat Sementioning
confidence: 99%
“…In order to solve the problems of GA for global optimization, Differential Evolution (DE) was proposed by Stron and Price [18,20]. Many studies have confirmed that DE is a more powerful optimization algorithm than GA, both in computation efficiency and accuracy [15,19,20,28]. Therefore, DE is employed in this paper to solve the optimization problem shown in Eq.…”
Section: Parameter Optimization Of Morlet Wavelet Filter and Flat Sementioning
confidence: 99%
“…In Mezura-Montes et al [31] and Zhang et al [78], DE variants for constrained optimiziation are proposed and analyzed. In Storn [60], Karaboga and Cetinkaya [18,19] a filter design is carried out by DE. In Onwubolu [43], DE is hybridized with group method of data handling for tool wear modelling and tine series prediction.…”
Section: Introductionmentioning
confidence: 99%
“…One of the first application domains for DE has been signal processing and more specifically the design of a digital filter, see [5]. Many other studies have shown the efficiency of this algorithmic structure in handling these problems, as shown in [6], [7], and [8]. A comparative study focussing on the capability of DE schemes of handling non-standard filter design problems has been presented in [9].…”
Section: Introductionmentioning
confidence: 99%